Analysing the integration of different types of energy and reserve providers in a competitive electricity supply market - Toh, Guen Keng (2014)
Deregulation of the electric power industry has unbundled a single electric power entity into separate business entities in the past two decades in many developed countries. The introduction of competition in the electricity market allows generation plants of different types, inclusive of renewable energy, and demand side management (DSM) to offer their energy and reserve. The main objectives of this new electric power industry are to reduce the cost that the consumers have to pay for electricity and to alleviate damage on the environment from electric power production. The choice of fundamental energy resources for generation has become an important factor in energy planning, since their availabilities and cost of extraction have a direct effect on the selection of generation types for electricity generation to achieve the objectives of the new electric power industry. The operating characteristic of these generation types is another factor that will influence the overall operating efficiency of the electric power system.